2023
DOI: 10.20944/preprints202304.0709.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Relationship between Psychological Needs and Sport Adherence for Students Participating in Physical Education Class

Abstract: The satisfaction of basic psychological needs leads students to engage in a sport modality on their own initiative. In the Spanish public educational system, mixed and heterogeneous, the gender and sport experience of students influence the teaching and motivation of invasion sports. This study investigated whether students' gender and sport experience, and method influence the psychological variables (basic psychological needs and sport adherence) when teaching school soccer and basketball. Furthermo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 36 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…The participating boys reported greater autonomy in the invasion sports of soccer and basketball. In contrast to this study, García-Ceberino, et al [1] reported that gender influenced perceived competence and students' intentionality to continue playing soccer in and out-of-school, in favor of boys. Gender-based analysis in another study [39] reported higher BPNs satisfaction and higher intention to be physically active associated with boys (PE students).…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The participating boys reported greater autonomy in the invasion sports of soccer and basketball. In contrast to this study, García-Ceberino, et al [1] reported that gender influenced perceived competence and students' intentionality to continue playing soccer in and out-of-school, in favor of boys. Gender-based analysis in another study [39] reported higher BPNs satisfaction and higher intention to be physically active associated with boys (PE students).…”
Section: Discussioncontrasting
confidence: 98%
“…Experienced students reported greater sport adherence in the invasion sports of soccer and basketball; however, there were no significant differences in three BPNs. A previous study [1] reported that the initial experience influenced the students' interest in continuing to play soccer in and out-of-school, but it did not influence their perceived competence. On the contrary, Heredia-León, et al [42] reported that students who participated in extracurricular activities (i.e., out-of-school) were associated with self-determined profiles.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations